Architectural Tourism Building for Urban Travel Destinations - Specht, Jan.; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
Since the early times of travelling architecture does constitute an important force of attraction and a vital element in marketing. Until today destinations try to increase their market positions by means of the development and restoration of the built environment. However, architecture is characterised by an enduring presence with impacts on visitors and residents alike. Hence, on a sustainable basis it needs to chime with place and situation. Where modesty might be suitable for one destination, spectacular architecture could be a transformation catalyst or unique selling proposition for another. Destination developers have to be aware of the local requirements as well as the reciprocal relationship between the modern practice of tourism and the built environment. To address the complexity of architectural tourism, throughout the book this topic is subject of a controversial discussion and approached with a contextual and interdisciplinary view. Contents Tourism and the Built Environment Architectural Tourism in the Spatial and Temporal Urban Context Contemporary Architecture and the Destination Image Architectural Tourism and the Spectaculture Target Groups Researchers, lecturers and students of tourism, architecture, urbanism and marketing Planners, developers, marketers and managers of travel destinations, Tourists interested in architecture About the Author Dr. Jan Specht is Professor of Business Administration at IUBH International University in Munich, Germany. He is head of the degree programme (3z(BTourism Management(3z(B.s
Tourism and the Built Environment -- Architectural Tourism in the Spatial and Temporal Urban Context -- Contemporary Architecture and the Destination Image -- Architectural Tourism and the Spectaculture.
Keywords: Economics; Architecture; Economics/Management Science; Tourism Management; Architecture, general; Urbanism